Political repression in Uzbekistan and peculiarities of the work of law enforcement agencies (1936-1938) - ERMETOV, AVAZ ABDULLAYEVICH (The journal of contemporary issues in business and government, 2021)
The article discusses political repression in Uzbekistan and peculiarities of the work of law enforcement agencies (1936-1938). The analysis of historical processes shows that certain methods and tools lie in the genesis of the formation of any statehood and the strengthening of the management system. This article analyzes the results of the latest research and reveals the history of that period in a transparent way.